First case of Ehrlichia canis infection in the common pipistrelle bat (Pipistrellus pipistrellus). Issue 4 (20th September 2021) - Selmi, Rachid; Belkahia, Hanène; Dhibi, Mokhtar; Ben Said, Mourad; Messadi, Lilia
Abstract: The present case report investigates the infection of a common pipistrelle bat ( Pipistrellus pipistrellus ) with various vector‐borne bacteria in northern Tunisia. The examined bat was found to be infested with the rat flea Xenopsylla cheopis and the specific bat mites Macronyssus spp. Spleen, liver and heart samples and ectoparasites were tested by polymerase chain reaction (PCR) assays targeting major vector‐borne bacteria. Only DNA of Anaplasmataceae bacteria was detected in spleen, liver and flea samples. Phylogenetic analysis of the 16S rRNA sequence obtained in this study suggested that this bat was infected with a specific Ehrlichia canis strain previously detected in domestic and wild canids and their associated ticks. We reported here the first case of infection with Ehrlichia canis in a bat. Hence, further studies must be undertaken to elucidate the potential role of bats in the epidemiology of this vector‐borne bacteria.